Principal Collaborative Leadership and Level of Job Satisfaction Among Primary School Teachers - Zainal Abidin, Nuramalina; Salwana Alias, Bity (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
Headmaster collaborative leadership is important because this practice is able to contribute to the level of teachers’ job satisfaction which is still an issue in the world of education to this day. This study was conducted to identify the collaborative leadership practices of headmasters and its relationship with to the level of teachers’ job satisfaction in Kota Tinggi, Johor. This study is a survey using a quantitative approach. The respondents of the study consisted of 226 primary school teachers. Descriptive and inferential analysis using SPSS software was used to answer the research questions. The findings showed that the level of collaborative leadership of headmasters as a whole was at a very high level (mean = 4.45, s.p. = 0.71), while the level of job satisfaction of teachers was at a very high level (mean = 4.23, s.p. = 0.71). Analysis through a Pearson Correlation test also showed that there was a significant and strong positive relationship between the collaborative leadership of Headmaster and the level of teachers’ job satisfaction (r = 0.628, p <0.01). The implication is that the Ministry of Education (MOE) needs to review the conditions for the appointment of headmasters by improving the policy of the National Professional Qualification for Educational Leaders (NPQEL) to ensure that every leader is skilled in practicing collaborative leadership. In conclusion, collaborative leadership practiced by headmasters is seen as an ideal leadership style and able to increase the level of job satisfaction of teachers.